2010
DOI: 10.1016/j.taap.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effects of Mn2+ on oxidative phosphorylation in liver, brain, and heart mitochondria using state 3 oxidation rate assays

Abstract: Manganese (Mn) toxicity is partially mediated by reduced ATP production. We have used oxidation rate assays -a measure of ATP production -under rapid phosphorylation conditions to explore sites of Mn 2+ inhibition of ATP production in isolated liver, brain, and heart mitochondria. This approach has several advantages. First, the target tissue for Mn toxicity in the basal ganglia is energetically active and should be studied under rapid phosphorylation conditions. Second, Mn may inhibit metabolic steps which do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 57 publications
(70 reference statements)
4
53
0
5
Order By: Relevance
“…Given the differential distribution of the two isoenzymes , this could result in differential vulnerability of different tissues to Mn. This is also consistent with the fact that mitochondrial function is differentially affected by Mn in various tissues (Gunter et al, 2010).…”
Section: Article In Presssupporting
confidence: 89%
“…Given the differential distribution of the two isoenzymes , this could result in differential vulnerability of different tissues to Mn. This is also consistent with the fact that mitochondrial function is differentially affected by Mn in various tissues (Gunter et al, 2010).…”
Section: Article In Presssupporting
confidence: 89%
“…It was earlier found that the inhibition of MPTP by Sr 2+ and Mn 2+ resulted in interaction of these metal ions with Ca 2+ sites facing the matrix [4,5,7,8,38,43]. However, bivalent metal ions such as Sr 2+ [14,26,50], Ni 2+ [30], Ba 2+ [13], Mn 2+ [9,15,28], as well as RR [43,62,66] can decrease the release of Ca 2+ from the mitochondrial matrix. The mitochondrial K + /H + antiporter was inhibited by these metal ions in a lot of Mn 2+ b Ca 2+ b Mg 2+ b Sr 2+ ( [67] and reference inside).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Ca 2+ [8,9] as well as Sr 2+ , Ba 2+ , and Mn 2+ [10][11][12][13][14][15][16] but not Ni 2+ [17] or La 3+ [18][19][20] are transported in the matrix via the mitochondrial calcium uniporter (MCU). The influence of these cations on mitochondrial Ca 2+ uptake depends on their ionic crystal radii [20,21] and hydration enthalpy [22].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinsonism and dystonia are common as sequelae of Mn, cyanide and carbon monoxide (CO) intoxications (Borgohain et al 1995;Calne et al 1994;Carella et al 1988;Choi 1983;Lee and Marsden 1994). Why Mn is able to produce the same effects that those substances is not known but there may be common mechanisms of injury; for example all of them are able to produce alterations in oxidative phosphorylation (Gunter et al 2010;Iheagwara et al 2007;Leavesley et al 2010) and both Mn and CO induce mPT and ROS production (Piantadosi et al 2006;Rao and Norenberg 2004).…”
Section: Manganese Mitochondria and Oxidative Damagementioning
confidence: 99%